Seismic assessment of three-storey residential buildings in Nepal - Chaulagain, H. (2014)
This paper evaluates the seismic performance of existing three-storey residential reinforced concrete (RC) buildings in Nepal. For this, it was designed a representative RC building structure (WDS) and the results were compared with similar buildings detailed with: i) Current Construction Practices (CCP); ii) Nepal Building Code (NBC) and iii) Modified Nepal Building Code (NBC+) recommendations. The results were analyzed and compared in terms of capacity curve, inter-storey drift and detailing of structures. The overall comparison indicates that CCP structure has a low amount of reinforcement both in beam and column sections when compared with the WDS structure. For the structure designed according with the NBC and NBC+ recommendations, improvements are clear relatively to the CCP structure, but it may be not sufficient for the demands in regions with high seismic hazard. Non-linear analysis shows that CCP and NBC structures experiences lower base shear capacity with higher inter-storey drift demand than other structures. Finally, the influence of seismic zone factor on reinforcement demand of the structure is analysed by designing the same WDS structure for a low, medium and high seismic hazard zone.